Laparoscopic resection of gastric GISTs. Where do we stand now? A single-centered experience - Iulian Slavu; Lucian Alecu; Adrian Tulin; Dana L. Stanculeanu; Cornelia Nitipir (Journal of Mind and Medical Sciences, 2019)
Introduction. Gastrointestinal stromal tumors (GISTs) represent a rare type of gastrointestinal neoplasms. Resection with negative margins has been established as a mainstay treatment, but laparoscopic resections are still open to debate. Material and method. This retrospective study was conducted at a single institution, with data collected over 2 years (01.01.2017-01.01.2019). The variables examined were age, tumor location with regard to the gastric wall, the results of the intraoperative endoscopy, intraoperative and postoperative complications, the surgical technique, and histopathological reports. Results. We identified 12 relevant cases, of which 8 were females and 4 males. The average tumor diameter was 2.3 cm. The majority of the lesions were located on the anterior gastric wall (8 cases), on the small curvature (2 cases), and in the pyloric region (2 cases). Intraoperative endoscopy was performed successfully in 10 cases in order to identify the lesions and guide the resection. The average operative time was 120 minutes and the average hospital stay was 5 days. The gastric wall with the lesion was resected using an Ultrasonic device, a 2-cm oncological safety margin was preserved. Conclusion. Complete surgical resection independent from the tumor size represents the current optimal treatment. From a surgical point of view, these tumors must be considered malignant and the surgeon must respect principles of oncological surgery. Maintaining tumor integrity at dissection is critical for the patient’s long-term prognosis. Laparoscopic resection independent of the tumor size is feasible.